2006
DOI: 10.1107/s1600536806005241
|View full text |Cite
|
Sign up to set email alerts
|

catena-Poly[[[(3,5-dimethyl-1H-pyrazole-κN2) copper(II)]-μ-[(3,5-dimethyl-1H-pyrazol-1-yl)methylamino]acetato] nitrate monohydrate]

Abstract: In the title complex, {[Cu(C8H12N3O2)(C5H8N)]NO3·H2O}n, the Cu atom is coordinated by two [(3,5‐dimethyl‐1H‐pyrazol‐1‐yl)methyl­amino]acetate anions and one 3,5‐dimethyl‐1H‐pyrazole ligand. There is one nitrate anion and one water mol­ecule in the asymmetric unit. The crystal packing is stabilized by N—H⋯O and O—H⋯O hydrogen bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…23 Complexes CuA and CoB have been structurally characterized by single crystal X-ray crystallography. The first complex CuA crystallizes in the monoclinic with the space group of C 2/c, a = 24.440(2) Å, b = 6.9711(6) Å, c = 23.924(2) Å, α = 90°, β = 119.728(6) Å and γ = 90° as it has been reported previously by Bolte et al 20 An ORTEP view of the cationic complex is shown in Figure 1.…”
Section: X-ray Crystallographymentioning
confidence: 68%
See 1 more Smart Citation
“…23 Complexes CuA and CoB have been structurally characterized by single crystal X-ray crystallography. The first complex CuA crystallizes in the monoclinic with the space group of C 2/c, a = 24.440(2) Å, b = 6.9711(6) Å, c = 23.924(2) Å, α = 90°, β = 119.728(6) Å and γ = 90° as it has been reported previously by Bolte et al 20 An ORTEP view of the cationic complex is shown in Figure 1.…”
Section: X-ray Crystallographymentioning
confidence: 68%
“…Precipitation in water, filtration of compounds AH and BH, followed by washing with cold water to eliminate solvent and unreacted starting materials (Scheme 1). Although it has been reported by our group that the ligand AH was purified and well characterised with its Cu(II) complex [20], It is too difficult to see on TLC or to separate the ligands AH and BH before their coordination to Cu(II) or Co(II) cations. So no ligands AH and BH gave satisfactory individual spectroscopic analysis.…”
Section: Synthesismentioning
confidence: 99%
“…The CSD Refcodes presenting in each type of topology are listed below: CICZUJ[64]OGALEO[71]FEGGAA[78]MEFZUS[87]VIKCOI[97]CEYLOI[104]PIFBAI[65]OGALIS[71]FOHFUE[79]MENGAO[88]VIQYEA[98]ECULUK[105]PODZOY[66]OKEHIV[72]GOYSES[80]NENDAL[89]VIQYIE[98]OKEHIV01[67]AVUPUC[67]OKEHOB[72]GOYSIW[80]NIQGUQ[90]WUPHEU[99]RAJNOG[106]AVUQOX[67]VOBKUT[73]HIHJIS[81]PAJJOA[91]XIBPAA[100]KOBGUE[40]DOGMAO[68]
…”
Section: One-dimensional Coordination Chainsmentioning
confidence: 99%
“…For related literature on metal oxalates and 1H-pyrazole complexes, see: Abdeljalil et al (2006); Bataille & Louë r (1999); Castillo et al (2001); Naumov et al (1995); Raptis et al (1999);Strotmeyer et al (2003); Tomyn et al (2007); Warda (1998).…”
Section: Related Literaturementioning
confidence: 99%
“…1H-Pyrazole and its 3,5-substituted derivatives have been widely used as bridging ligands in molecular magnetism and supramolecular chemistry for obtaining discrete oligonuclear complexes of high nuclearity and coordination polymers (Abdeljalil et al, 2006;Raptis et al, 1999;Warda, 1998). On the other hand, oxalate is an important polynucleative ligand as it can exhibit various bridging modes, which, together with the varied coordination preferences of metal ions, can result in the formation of oligonuclear species or compounds containing one-, two-and three-dimensional coordination polymers and frameworks (Castillo et al, 2001;Naumov et al, 1995;Bataille & Louër, 1999;Strotmeyer et al, 2003;Tomyn et al, 2007).…”
Section: S1 Commentmentioning
confidence: 99%